2015
DOI: 10.1083/jcb.201505091
|View full text |Cite
|
Sign up to set email alerts
|

Reversible ubiquitination shapes NLRC5 function and modulates NF-κB activation switch

Abstract: Reversible ubiquitination strictly controls NLRC5 function: K63-linked ubiquitination of NLRC5 at lysine 1,178 mediated by TRAF2/6 generates a coherent feedforward loop to sensitize switch-like activation of NF-κB, whereas USP14 specifically removes the polyubiquitin chains from NLRC5 to enhance NLRC5-mediated inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 47 publications
2
51
0
Order By: Relevance
“…But Meng et al. showed that USP14 negatively regulates NF‐кB signaling by removing the polyubiquitin chains from NLRC5 to enhance NLRC5‐mediated inhibition of NF‐κB activation . We discovered that USP14 suppressed VSV‐induced RIG‐I activation through deubiquitinating K63‐linked RIG‐I.…”
Section: Discussionmentioning
confidence: 82%
“…But Meng et al. showed that USP14 negatively regulates NF‐кB signaling by removing the polyubiquitin chains from NLRC5 to enhance NLRC5‐mediated inhibition of NF‐κB activation . We discovered that USP14 suppressed VSV‐induced RIG‐I activation through deubiquitinating K63‐linked RIG‐I.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, Meng's research found that ubiquitination editing of NLRC5 determined NLRC5-IKKβ interaction dynamics and enhanced the activation of NF-κB signaling [27]. Protein ubiquitination is an exceptionally flexible posttranslational modification which regulates a wide variety of signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…USP14 is one of three proteasome-associated deubiquitinating enzymes that remove ubiquitin from proteasomal substrates prior to their degradation [31]. USP14 specifically removes the polyubiquitin chains from NLRC5 to enhance the interaction between NLRC5 and IKK-β, thus inhibiting NF-κB activation in an NLRC5-dependent coherent feedforward loop (CFL) manner [27]. Given that NLRC5 is involved in many biological processes and functions as a negative regulator of NF-κB and PI3K/Akt signaling pathways, we hypothesized that NLRC5 negatively regulates the titanium particles-induced osteolysis in vitro and in vivo, which is enhanced by USP14.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations